황사 배출량이 동아시아 지역 PM10 농도에 미치는 영향 - 최대련(Dae-Ryun Choi); 구윤서(Youn-Seo Koo); 조진식(Jin-Sik Jo); 장영기(Young-Kee Jang); 이재범(Jae-Bum Lee); 박현주(Hyun-Ju Park) (한국대기환경학회지(국문), 2016)
The anthropogenic aerosols originated from the pollutant emissions in the eastern part of China and dust emitted in northwestern China in Yellow sand regions are subsequently transported via eastward wind to the Korean peninsula and then these aerosols induce high PM10 concentrations in Korean peninsula. In order to estimate air quality considering anthropogenic and dust emissions, Comprehensive Air-quality Model with extension (CAMx) was applied to simulate PM10 concentration. The predicted PM10 concentrations without/ with dust emissions were compared with observations at ambient air quality monitoring sites in China and Korea for 2008. The predicted PM10 concentrations with dust emissions could depict the variation of measured PM10 especially during Yellow sand events in Korea. The comparisons also showed that predicted PM10 concentrations without dust emissions were under-predicted while predictions of PM10 concentrations with dust emission were in good agreement with observations. This implied that dust emissions from desert and barren soil in southern Mongolia and northern China minimized the discrepancies in the PM10 predictions in East Asia. The effect of dust emission on annual PM10 concentrations in Korea Peninsula for year 2008 was 5~10 μg/m3, which were about 20% of observed annual PM10 concentrations. KCI Citation Count: 4